Priority areas for increasing the competitiveness of the real sector of the economy of the Republic of Belarus - Palonik, Stiapan S.; Smaliarova, Maryna A. (Journal of the Belarusian State University. Economics, 2018)
The scientific article analyzes the structure of the Belarusian economy, determines its competitive advantages, elaborates the main directions for increasing competitiveness and priorities for the transformation of the real sector of the economy of the Republic of Belarus. The sources of potential advantages, factors of their creation and implementation are specified. The role, functions and place of the real sector of the economy of the Republic of Belarus are determined.
Keywords: level of competitiveness; competitive advantages; potential; structure of the economy; transformation; modernization; management; real sector of the economy